AN ANALYSIS OF THE ABILITY OF THE SECOND YEAR STUDENTS OF SMKF IKASARI PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Delvi Janrianingsih; Fadly Azhar; Supriusman Supriusman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was designed to describe the students’ ability in comprehending recount texts and aimed at finding out the ability of the second year students of SMKF Ikasari Pekanbaru in comprehending recount texts. The sample was XI.5-Pharmacy (38 students) chosen by cluster random sampling technique. The result showed that the reading ability of the second year students of SMKF Ikasari pekanbaru in comprehending recount text is in good level with the mean score was 61. However, this score was lower than the minimum score criteria(75). The most difficult aspect in comprehending recount text was in making inferences (46.1). Then, the easiest aspect was in finding factual information (83.6). Then, the students’ mean score in term of finding main idea was 65.8. The students’ mean score in term of finding references and finding the meaning of difficult word was same; it was 57.9. The students’ mean score in term of finding generic structure, with the mean score was 50. And the students’ mean score in term of finding social function of recount text was 55.3. The last, the students’ mean score in term of finding language features of recount text was 71.1.Therefore, this research suggested that the English teachers to focus on the components where students still find it difficultt and the students should learn that texts for better comprehension of other reading texts.Key Words: Student’s Ability, , Comprehending Recount Texts.